Analysis Of The Determinants Of Electrical Energy Consumption In The Period Of 2017 – 2023 (Case Study Of Provinces In Indonesia) - Siti Naeni Nur Khaeni; Hastarini Dwi Atmanti (Publikasi Inspirasi Indonesia, 2024)
The purpose of this study is to examine the variables influencing Indonesia's electrical energy consumption from 2017 to 2023. Utilising secondary data from Central Bureau of Statistics of Indonesia and State Electricity Company (PLN) for the years 2017– 2023, quantitative research using a regression analysis approach is the study methodology employed. The population, income per capita, information technology development index, and human development index are the independent variables in this study. The population, human development index, and per capita income all had a significant impact on the amount of electrical energy used, according to the findings. In the meanwhile, there is a slight but negative impact from the information technology development index. Together, the independent factors can account for 88.6% of the fluctuation in Indonesia's electrical energy usage. According to the study's findings, increasing electrical energy.